Can Mobile Learning Be An Opportunity for Undergraduate Teacher Education? - Eroğlu, Mehmet; Vildan Donmuş Kaya; Ramazan Özbek (European Journal of Social Science Education and Research, 2019)
The purpose of research is to determine the usability of mobile learning in undergraduate teacher education. In the first part of the study, researches on mobile learning opportunities in undergraduate teacher education and teacher education are examined. In the second part of the study, infrastructure and readiness for mobile learning of prospective teachers are examined in terms of some variables. The research is designed in survey model. The sample of the research is composed of 454 prospective teachers who study in the 1st and 4th grade of Firat University Faculty of Education. Participant demographic form and the readiness scale for mobile learning developed by Lin, Lin, Yeh and Wang (2016) adapted to Turkish by Gökçeaslan, Solmaz and Kukul (2016) is used as data collection tool. Statistical techniques such as mean, frequency, percentage, t test, one way anova are used in the analysis of the data. The research findings revealed by examining the relevant researches show that mobile learning offers important opportunities for undergraduate teacher education. Prospective teachers have mobile tools necessary for mobile learning and have opportunities access to internet. It is determined that prospective teachers frequently use mobile tools and use mobile tools partially for educational purposes. It is determined that the level of prospective teachers' readiness for mobile learning has partially high (= 3.60) and the level of prospective teachers' readiness for mobile learning is not differ according to gender, educational level and department variables. But prospective teachers' readiness for mobile learning differs according to the daily average internet usage time. The results of the research show that mobile learning is an approach that should be taken into account for undergraduate teacher education.
Keywords: Mobile learning, readiness for mobile learning, undergraduate teacher education.